Communication Strategy In Achieving Sustainable Environmental Development: Case Study Of The Ban On The Use Of Plastic Bags In Familymart Retail Stores - Anwar, Nugra P.; Sitorus, Hema Junaice; Tanoyo, Mellysa; Setijadi, Naniek Novijanti (CV. ITTC INDONESIA, 2024)
This study explores the communication strategies utilized by FamilyMart retail stores to enforce the ban on plastics bags, aiming to support sustainable environmental development. As environmental concerns become increasingly significant, retail businesses are at the forefront of promoting sustainable practices. This research investigates how FamilyMart conveys its environmental policies to customers and the broader community to encourage behavior change towards eco-friendly alternatives. Using qualitative methods, the research involves in-depth interviews with store managers, content analysis of promotional materials, and observations of in-store communication efforts. According to the research, FamilyMart has a thorough communication strategy that consists of educational initiatives for customers, conspicuous signage, and active participation on social media. These tactics aim to encourage consumers to use reusable bags by raising awareness of the negative environmental effects of plastic bag usage. Effective communication strategies make use of visual aids, customer incentives for program involvement, and compelling and informative messaging. The report also emphasizes how crucial it is to use consistent messages throughout a range of communication channels and how important employee involvement is to achieve the initiative's goals. The findings show that establishing a sustainable culture and obtaining consumer compliance depend heavily on efficient communication. The report ends with actionable suggestions for retailers looking to put similar environmental policies into place. These suggestions emphasize the importance of using multifaceted, transparent, and engaging communication tactics to support long-term, sustainable change.